Resection and repair of a Cas9 double-strand break at CTG trinucleotide repeats induces local and extensive chromosomal deletions. - Valentine Mosbach; David Viterbo; Stéphane Descorps-Declère; Lucie Poggi; Wilhelm Vaysse-Zinkhöfer; Guy-Franck Richard (PLoS Genetics)
Microsatellites are short tandem repeats, ubiquitous in all eukaryotes and represent ~2% of the human genome. Among them, trinucleotide repeats are responsible for more than two dozen neurological and developmental disorders. Targeting microsatellites with dedicated DNA endonucleases could become a viable option for patients affected with dramatic neurodegenerative disorders. Here, we used the Streptococcus pyogenes Cas9 to induce a double-strand break within the expanded CTG repeat involved in myotonic dystrophy type 1, integrated in a yeast chromosome. Repair of this double-strand break generated unexpected large chromosomal deletions around the repeat tract. These deletions depended on RAD50, RAD52, DNL4 and SAE2, and both non-homologous end-joining and single-strand annealing pathways were involved. Resection and repair of the double-strand break (DSB) were totally abolished in a rad50Δ strain, whereas they were impaired in a sae2Δ mutant, only on the DSB end containing most of the repeat tract. This observation demonstrates that Sae2 plays significant different roles in resecting a DSB end containing a repeated and structured sequence as compared to a non-repeated DSB end. In addition, we also discovered that gene conversion was less efficient when the DSB could be repaired using a homologous template, suggesting that the trinucleotide repeat may interfere with gene conversion too. Altogether, these data show that SpCas9 may not be the best choice when inducing a double-strand break at or near a microsatellite, especially in mammalian genomes that contain many more dispersed repeated elements than the yeast genome.